From Ta-Kesh to Ta-Kush: The affordances of digital, haptic visualisation for heritage accessibility. (December 2020) - Smith, Kathryn; Roughley, Mark; Harris, Samantha; Wilkinson, Caroline; Palmer, Evelyn
Abstract: This paper describes the 3D facial depiction of a 2700-year-old mummy, Ta-Kush, stewarded by Maidstone Museum, UK, informed by new scientific and visual analysis which demanded a complete re-evaluation of her biography and presentation. The digital haptic reconstruction and visualisation workflow used to reconstruct her facial morphology is described, in the context of the multimodal and participatory approach taken by the museum in the complete redesign of the galleries in which the mummy is displayed. Informed by contemporary approaches to working with human remains in heritage spaces, we suggest that our virtual modelling methodology finds a logical conclusion in the presentation of the depiction both as a touch-object as well as a digital animation, and that this 'digital unshelving' enables the further rehumanization of Ta-Kush. Finally, we present and reflect upon visitor feedback, which suggests that audiences respond well to interpretive material in museums that utilizes cutting-edge, multimedia technologies. Graphical abstract: Image 1 Highlights: Biomedical imaging and scientific analysis of mummified remains produces new knowledge. Haptically-enabled digital 3D workflow for facial depiction embodied in museum 'touch-object'. Non-destructive imaging does not equal claims to 'non-invasiveness' in relation to human remains. Creative collaboration results in innovation and positive visitor feedback despite small budget.